Application of geoprocessing techniques in the selection of suitable areas for landfill implantation in the Portal do Pantanal (Research, Society and Development, 2021)
The management and improper disposal of solid waste can cause social and environmental impacts, such as soil degradation and water bodies compromise. The objective of this research was to elaborate an aptitude map for landfill implantation in Coxim Municipality, located in Mato Grosso do Sul State, which has a strategic position for conversation of Cerrado and Pantanal natural resources. As methodology was applied the Hierarchical Analysis, considering the following factors: slope; hydrography; land use and occupation; vegetation; and road network. The ArcGis Geographic Information System platform was used for the elaboration of the maps and for the Multicriteria Analysis, which involved the aforementioned factors, which resulted in the suitability map for the installation of landfills in the municipality. It was concluded that 45% of the area of the municipality is able to receive a landfill. These results, if applied to the urban and environmental management of the municipality, may reduce the costs with final logistics of urban solid waste and thus reduce the ecological footprint of management processes.